2006
DOI: 10.1074/jbc.m512980200
|View full text |Cite
|
Sign up to set email alerts
|

Versican G3 Domain Regulates Neurite Growth and Synaptic Transmission of Hippocampal Neurons by Activation of Epidermal Growth Factor Receptor

Abstract: Versican is one of the major extracellular matrix (ECM) proteins in the brain. ECM molecules and their cleavage products critically regulate the growth and arborization of neurites, hence adjusting the formation of neural networks. Recent findings have revealed that peptide fragments containing the versican C terminus (G3 domain) are present in human brain astrocytoma. The present study demonstrated that a versican G3 domain enhanced cell attachment, neurite growth, and glutamate receptor-mediated currents in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 66 publications
0
50
0
1
Order By: Relevance
“…Additionally, these authors demonstrated that versican isoforms could increase EGFR levels in glioma cells and signal through EGFR activation in neural cells (35)(36)(37). This prompted us to investigate whether EGFR signaling could mediate the brevican-dependent increase of fibronectin in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, these authors demonstrated that versican isoforms could increase EGFR levels in glioma cells and signal through EGFR activation in neural cells (35)(36)(37). This prompted us to investigate whether EGFR signaling could mediate the brevican-dependent increase of fibronectin in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, V3-expressing ASMCs had reduced levels of PI3K p85 downstream of EGFR, indicating that the blockade of EGFR-dependent signaling may be partially due to decreases in signaling mediators. Because V3 has EGF-like motifs that have been shown to affect EGF-dependent signaling pathways (72)(73)(74), the blockade of EGFR-dependent signaling might be mediated by the G3 domain within V3. These possibilities are currently under investigation.…”
Section: V3 Resists Monocyte Adhesion By Altering Signaling Pathwaysmentioning
confidence: 99%
“…Versican protein has a complex structure, including a highaffinity hyaluronan binding N-terminal domain, a densely chondroitin sulfate substituted midsection, and cell surface receptor-interacting functions, including reported abilities to activate toll-like receptors [27][28][29] and the EGFR [30][31][32]. Versican is widely expressed and mainly involved in tissue morphogenic processes, such as heart valve and limb morphogenesis [33][34][35], but it also promotes growth and metastasis of a range of carcinoma types [36].…”
Section: Introductionmentioning
confidence: 99%